BIMBINGAN TEKNIS PENULISAN ARTIKEL ILMIAH BAGI GURU-GURU SMP NEGERI 8 PALOPO, SULAWESI SELATAN - Baharuddin, Muhammad Rusli (Abdimas Siliwangi, 2020)
The partners in this Community Service activity are the teachers of Palopo 8 Public Middle School which are still not optimal in carrying out scientific research and publications. In general, the problem of partners, namely the number and quality of research and publications of teachers at scientific meetings is still not recorded from 49 teachers, only 5 have conducted research in schools, while for publication in scientific meetings only 3 teachers have attended national seminars. In addition, the activities of the subject teacher deliberation have not specifically led to the use of research results so that the pattern of teacher professional development is still not optimal. Based on the problems faced by partners, the PKM team offered a Solution, namely Classroom Action Research Training, Data Processing and Analysis Assistance, Technical Guidance for Writing Scientific Articles. The approach method used is Training, Assistance, Technical Guidance, and Monitoring the evaluation of the implementation of activities. The target of this PKM activity is an increase in teacher knowledge in carrying out Classroom Action Research, being able to process and analyze research data, being able to write scientific articles.